Methanolic extract of Justicia secunda ameliorates the cyclophosphamide-induced hepatic and renal failures in rats - Winner Oyidiya Kalu; Chinedum Ogbonnaya Eleazu; Ngozi Kalu Achi; Mercy Amarachi Iroaganachi; Duru Majesty (Avicenna Journal of Phytomedicine)
Objective: This study determined the effect of the methanolic extract of Justicia secunda against cyclophosphamide-instigated hepatic and renal toxicities in rats and analyzed the bioactive constituents of the extract using gas chromatography mass spectrophotometry (GC-MS). Materials and Methods: Twenty male albino Wistar rats were assigned into four groups of five rats each: Group 1 received rat feeds and tap water for 14 days. Group 2 received rat feeds and water for 14 days and cyclophosphamide (CPH, 100 mg/kg.BW) on day 15. Group 3 received rat feeds and 200 mg/kg.BW of the extract for 14 days and CPH on day 15 while Group 4 received rat feeds and 400 mg/kg.BW of the extract for 14 days and CPH on day 15.Results: CPH induction altered the final body weights, hepatic and renal total proteins, antioxidant markers, liver and kidney weights, and serum transaminases, urea, and creatinine concentrations of the rats, inducing lipid peroxidation in them which was mitigated following supplementation with J. secunda. GC-MS assay showed the presence of twenty compounds in J. secunda extract and acute toxicity study (using mice to determine the safety profile of the extract) showed the safety of the usage of the plant at 200 and 400 mg/kg doses.Conclusion: J. secunda has protective effects against CPH-induced hepatic and renal toxicities which could be attributed to its bioactive compounds.